PENGARUH SUPERVISI KEPALA SEKOLAH TERHADAP KINERJA GURU DI SMP NEGERI 1 PARUNG KECAMATAN PARUNG KABUPATEN BOGOR - Darmawati, Darmawati; Munjin, R. Akhmad; Seran, G. Goris (JURNAL GOVERNANSI, 2015)
The research method was associative. The data collection techniques used was literature and field studies. The study population amounted to 47 respondents. The sampling technique used was simple random sampling. Determination of the sample used Yamane formula so the result sampling was 32 respondents. To determine the degree of correlation was used Pearson Product Moment Correlation. The results of research recapitulation variable supervision showed the average score of 3.2 which categorized medium and the recapitulation teacher performance variables obtained an average score 4.45 which categorized very good, the product moment correlation significance test for n = 32 , standard error of 5%, then the value of rtable=0.349. then   rcount  0.195 the count was less than rtable=0.349, so 0.195 was a significant correlation coefficient. The research conclusion showed that the influence of principal supervising toward teacher performance by 19.5% and the remaining 80.5% was determined other factors, such as the assessment of teachers by students, delivery of teaching material according to the students opinion, incentives, teacher certification.   Key word: Supervision, Performance, Teacher.